The correlation between anxiety and depression levels with bulimic symptomatology and body mass index during COVID-19 quarantine measures: A 2-month follow-up study - Erdoğan Kaya, Ayşe; Turan, Çağlar; Oğur, Yavuz Selim; Yavaş, Nurullah; Erol, Atila (The European Research Journal, 2025)
Objective: This study aims to investigate the relationship between anxiety and depression levels with bulimia symptoms and body mass index (BMI) during the quarantine measures. Methods: Voluntary individuals were included, and individuals were evaluated before and after 2-month quarantine period, and self-report questionnaires were administered. In addition to the sociodemographic data form, Hospital Anxiety and Depression Scale (HADS) and Bulimic Investigatory Test, Edinburgh (BITE) were applied twice to the participants and their BMI were recorded. Results: An increase in HADS-A scores was observed after quarantine (z=-6.456, P